Treatment Experience Using a Stent Graft for Lumbar Artery Injury that Failed Coil Embolization - Kim, Gil H; Lee, Sang B; Park, Chan I; Kim, Jae H; Kim, Chang W (Journal of Endovascular Resuscitation and Trauma Management, 2024)
Transcatheter embolization currently constitutes the primary treatment for lumbar artery injury due to blunt trauma. We present a case where a stent graft effectively treated a lumbar artery injury after coil embolization failed to achieve hemostasis. Aortic stent graft implantation is a safe procedure that can prevent surgical morbidity and has minimal complications. It may serve as an effective alternative for achieving hemostasis when coil embolization is not feasible or is unsuccessful.